2024
DOI: 10.26599/fshw.2022.9250121
|View full text |Cite
|
Sign up to set email alerts
|

Response and assembly of abundant and rare taxa in Zaopei under different combination patterns of Daqu and pit mud: from microbial ecology to Baijiu brewing microecosystem

Abstract: The quality and aroma of strong-flavor Baijiu are mainly dependent on Daqu, pit mud (PM), and the interaction of both. However, little is known about how their combination patterns affect the microbiome and metabolome of Zaopei, especially the metabolic function of rare taxa. Here, an experiment on industrial size was designed to assess the effects of 6 combinations (3 kinds of Daqu × 2 kinds of PM) on the composition and assembly of different taxa, as well as the flavor profile. The results showed that Zaopei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 52 publications
0
2
0
Order By: Relevance
“…The TCA cycle, essential for aerobic respiration, plays a vital role in providing energy and nutrition for microbial growth and is primarily influenced by Abundant fungi . Meanwhile, the metabolism of the butyric acid pathway was strongly associated with the bacterial RT [ 4 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The TCA cycle, essential for aerobic respiration, plays a vital role in providing energy and nutrition for microbial growth and is primarily influenced by Abundant fungi . Meanwhile, the metabolism of the butyric acid pathway was strongly associated with the bacterial RT [ 4 ].…”
Section: Resultsmentioning
confidence: 99%
“…Daqu is an essential starter and one of the requisite raw materials in Baijiu brewing [ 3 ]. In fact, the contribution of the microbiota habituated in Daqu to the yield and quality of the fresh Baijiu still depended on the interaction with PM [ 4 ]. Previous studies revealed the synthesizing of some organic acids was driven by the synergistic effect of microbiota habiting in both FG and PM during the process [ 5 ].…”
Section: Introductionmentioning
confidence: 99%